Very mild cases of Rett syndrome with skewed X inactivation. Issue 10 (11th May 2006) - Huppke, P; Maier, E M; Warnke, A; Brendel, C; Laccone, F; Gärtner, J
Abstract : Background: Rett syndrome, a common cause of mental retardation in females, is caused by mutations in the MECP2 gene. Most females with MECP2 mutations fulfil the established clinical criteria for Rett syndrome, but single cases of asymptomatic carriers have been described. It is therefore likely that there are individuals falling between these two extreme phenotypes. Objective: To describe three patients showing only minor symptoms of Rett syndrome. Findings: The patient with the best intellectual ability had predominantly psychiatric problems with episodes of uncontrolled aggression that have not been described previously in individuals with MECP2 mutations. All three patients had normal hand function, communicated well, and showed short spells of hyperventilation only under stress. Diagnosis in such individuals requires the identification of subtle signs of Rett syndrome in girls with a mild mental handicap. Analysis of the MECP2 gene revealed mutations that are often found in classical Rett syndrome. Skewed X inactivation was present in all three cases, which may explain the mild phenotype. Conclusions: Because of skewed X inactivation, the phenotype of Rett patients may be very mild and hardly recognisable.